L’a b c della psicanalisi. Il tema della telepatia in Derrida - Vergani, Mario (Bollettino Filosofico, 2021)
The essay discusses the relationship between psychoanalysis and deconstruction through the subject of telepathy, defined by Derrida as “a.b.c. of the psychoanalysis”. It is divided into three moments. First of all, it analyses the derridean reading of Freud’s texts dedicated to telepathy; it shows, in second place, the long-distance relationships between several other thinkers who talk about this item. Finally, it points out some major themes on which Derrida’s reflections about telepathy focus: future, otherness, support, encounter, visitation. Keywords: Deconstruction, Derrida, Freud, Psychoanalysis, Telepaty